UNDERSTANDING THE DEFINITIONS OF CYBER TERRORISM WORLDWIDE AND REVIEWS OF RESEARCH STUDIES IN INDIAN CONTEXT AND HOW IMPORTANT IS THE STUDY OF CYBER TERRORISM IN INDIA - 1. Aditya Kumar , 2. Dr. Anand K. Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Prior to the 26/11 attacks, cyberterrorism was one of the most disregarded and undervalued issues in India. India has the maximum internet users, called as ‘Netizens’ after USA and China. There is a sizable, multidisciplinary body of research on cyberterrorism that has been expanding gradually since the early 1990s and took off after the horrifying Mumbai incident. The majority of Indians are indifferent to the dangers of being victims of cyberattacks. The words "cyber" and "terror" are combined to form the term "cyberterrorism." In India, cyberattacks on government, defence sector, and banking systems are becoming more frequent by the day. A comprehensive understanding of these areas is essential for India to secure its digital future, enhance its national security, and foster a resilient infrastructure capable of resisting cyber terrorism.